Studi Aliran Daya Sistem Tenaga Listrik Menggunakan Metode Gauss-Seidel - VICKY - SALAMENA (Jurnal ELKO (Elektrikal dan Komputer), 2024)
This study is a study of power flow in an electric power system consisting of three buses which aims to find the amount of power and voltage as well as the tension angles in each bus, as well as the power losses in each channel. Modeling of electric power systems for power flow studies produces mathematical equations that can be solved simultaneously. One numerical method to solve this problem is to use the Gauss-Seidel method.To solve the power flow, the system is assumed to operate in a three-phase balanced condition and modeling is carried out for one phase which represents the other two phases. This requires four quantities that exist on each bus, namely active power and reactive power that enter the bus with these two quantities known on each bus. The non-linear algebraic equations for the power flow model are solved numerically using the Gauss-Seidel method.From the iteration results, the voltage on bus 2 and bus 3 was  pu and  pu. The power provided by Slack-Bus is 409.5 MW and 189 MVAr. Power loss on line 1-2 is 8.5 MW + j17.0 MVAr, line 1-3 is 5.0 MW + j15.0 MVAr and line 2-3 is 0.8 MW + j1.60 MVAr.